The Federal Reserve and market confidence - Nina Boyarchenko; Valentin Haddad; Matthew C. Plosser (Federal Reserve Bank of New York, 2016)
We discover a novel monetary policy shock that has a widespread impact on aggregate financial conditions. Our shock can be summarized by the response of long-horizon yields to Federal Open Market Committee (FOMC) announcements; not only is it orthogonal to changes in the near-term path of policy rates, but it also explains more than half of the abnormal variation in the yield curve on announcement days. We find that our long-rate shock is positively related to changes in real interest rates and market volatility, and negatively related to market returns and mortgage demand, consistent with policy announcements affecting market confidence. Our results demonstrate that Federal Reserve pronouncements influence markets independent of changes in the stance of conventional monetary policy.
Keywords: E44; G12; G14; 330; policy announcement; risk premium; uncertainty; financial conditions